Effect of Bifidobacterium lactis HN019 on inflammatory markers and oxidative stress in subjects with and without the metabolic syndrome - Bernini, Luciana J.; Simão, Andréa N. Colado; de Souza, Cínthia H. B.; Alfieri, Daniela F.; Segura, Liliane G.; Costa, Giselle N.; Dichi, Isaias (British journal of nutrition, 2018)
Beneficial effects of probiotics have been reported on body weight, lipid and carbohydrate metabolism, inflammatory state and oxidative stress in healthy subjects and in many metabolic and inflammatory diseases. The aim of this study was to evaluate the effects of Bifidobacterium lactis HN019 on inflammatory state and nitro-oxidative stress in patients with and without the metabolic syndrome (MetS). The usual diets of the thirty-three subjects were supplemented with probiotic milk for 90 d. Inflammatory markers and oxidative measurements were performed. In relation to the baseline values, subjects in both groups showed a decrease in homocysteine (P=0·02 and P=0·03, respectively), hydroperoxides (P=0·02 and P=0·01, respectively) and IL-6 levels (P=0·02). Increases in adiponectin (P=0·04) and nitric oxide metabolites (NOx, P=0·001) levels were only seen in the group with the MetS in relation to the baseline values, whereas only the individuals without the MetS had increases in total radical-trapping antioxidant parameter levels (P=0·002). In conclusion, B. lactis HN019 have several beneficial effects on inflammatory and oxidative biomarkers in healthy subjects and the MetS patients. Patients with the MetS showed a specific improvement in adiponectin and NOx levels, whereas a specific favourable effect was shown in the antioxidant defenses in healthy subjects. If the results obtained in the present study are confirmed, supplementation of fermented milk with probiotics in healthy subjects and patients with the MetS must be further discussed.